Professional insertion in Veterinary Medicine: A look at the challenges faced by recent graduates (Research, Society and Development, 2025)
This study aimed to analyze the main difficulties faced by recently graduated veterinary physicians when entering the labor market, considering aspects related to academic training, professional requirements, and the socioeconomic conditions of the area. The research was developed based on a questionnaire applied to graduates of the Veterinary Medicine course in the state of Rondônia from both public and private universities, seeking to understand their perceptions of the initial challenges of labor market insertion. It was observed that the lack of practical experience during graduation, personal insecurity when facing clinical responsibilities, and the high market competitiveness are recurring factors that hinder the start of their careers. Furthermore, the necessary financial investment in complementary courses, specializations, and equipment is pointed out as a significant obstacle to professional consolidation. The study also found that institutional support for graduates is limited, making it necessary to strengthen educational policies aimed at the transition between academic life and professional practice. Residency programs, mentorships, and partnerships with the productive sector can represent effective strategies to reduce this gap.